Mars gets broadband connection. - Kumagai, J. (IEEE spectrum)
In addition to its mission of seeking out areas in Mars where water once flowed, identifying habitats where ancient life might have thrived, and mapping the entire planet in unprecedented detail, NASA's Mars Reconnaisance Orbiter will also set the stage for a new epoch in spacecraft telecommunications. Its onboard Electra UHF relay transceiver will serve as an engineering test bed for new communications and navigation technology that will be required for all future orbiters, landers, and rovers, to provide faster data rates required for transfer of information from rovers and landers on the Martian surface to orbiters circling above. Besides serving as a transceiver for all Mars missions, Electra will also provide a navigational or locational beacon for incoming spacecraft or any craft on the surface of Mars.